Políticas socioambientais na Amazônia: o projeto Bolsa Verde e a inclusão produtiva das famílias da Resex Médio Purus, Lábrea (AM) - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
Social and environmental policies emerged in Brazil, especially in the 90s to promote sustainable development in the country and contribute to environmental protection. Since then, the principles intended to promote sustainability have guided public policies and, from its institutional integration, they sought to eradicate poverty, to promote economic development and nature conservation in order to construct a sustainable production model that could integrate development both in urban and rural areas.The main objective of this thesis was to investigate the development of the PBV- Programa Bolsa Verde (Green Grant Program), created in 2011, by the Federal Government both as an environmental conservation strategy and as rural productive inclusion, besides learning about its implications in the ways of life and work of agroextractivist families from Cassianã community in Resex Middle Purus in Lábrea (AM ). Therefore, from an interdisciplinary approach, it was necessary to identify the context of the local people struggles, the social environmental demands and the environmental conflicts that have arisen as a result of government strategies for productive inclusion in the rural Amazon, considering the perspective of environmental conservation. The methodology used was based on the qualitative research, developed by collecting documentary and literature data, field research and local observation. Semi-structured interviews were conducted, through forms applied to 17 family units served by PBV and the collective elaboration of mental maps to identify the geographical and environmental characteristics of the agro-extractive system of Cassianã community. Still narrative interviews were carried out, using as instrument the self-generating scheme applied to the Resex Middle Purus manager and community leaders. The results indicate that, as one of the elements for rural productive inclusion and environmental conservation, PBV has no clear purpose as to its concept and methodology. Being a new, experimental government program, it needs to be well defined to be effective as a social environmental law policy for traditional people. Over the past years, through the process of environmental and reconstruction of socio-cultural identities, social and political struggles of the traditional peoples of the Amazon, the environmental conflicts have been put under discussion in the political arena, as an important strategy in the development and (re) construction of new territoriality that preserve ethnic and cultural identities, and guarantee the survival of ecosystems where traditional people live. In this context, the agroextractivist ecosystem of Cassianã community can be presented as an intimate relationship between man and nature. Its productive potential requires the urgent development of a management plan that enables an economically viable production chain, environmentally balanced and socially just, capable of generating life improvements for agroextractivist families. This will require breaking up with material and symbolic aspects of development established in the region. However, there have been some difficulties in carrying out the productive inclusion of PBV and the other programs related to it. Programs must also make a broad participation of agroextractivist possible, giving them voice and a greater autonomy in managing Resex Middle Purus, as well as they need to integrate temporal and effectively to the implementation of public policies that allow families access to social goods and services of citizenship.
Keywords: Inclusão produtiva; Conflitos socioambientais; Agroextrativismo; Reserva Médio Purus; CIÊNCIAS HUMANAS